2015
DOI: 10.1155/2015/586514
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Degradability of HDPE, LDPE, PE-BIO, and PE-OXO Films under UV-B Radiation

Abstract: The changes in structural properties of high density polyethylene films (HDPE), low density polyethylene films (LDPE), biodegradable polyethylene (PE-BIO), and oxodegradable polyethylene (PE-OXO) films exposed to UV-B radiation were studied. The carbonyl(ICO)and vinyl(IV)index, the crystalline phase fraction, and the dichroic ratio were used to evaluate the photooxidation of these polymers. The results obtained show that LDPE and HDPE undergo a major degree of oxidation and an increase in the crystalline phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 36 publications
1
52
0
4
Order By: Relevance
“…The absorption of energy by heating might cause reversible or irreversible modification of physical and chemical properties of samples by oxidation. Similar studies performed by ESR method on UV-irradiated polystyrene showed possible ionization and breaking of chemical bonds of the polymeric chains, [1]. Gamma irradiation of such materials induces a crystallization effect, as confirmed by NMR, [2].…”
Section: Introductionmentioning
confidence: 70%
“…The absorption of energy by heating might cause reversible or irreversible modification of physical and chemical properties of samples by oxidation. Similar studies performed by ESR method on UV-irradiated polystyrene showed possible ionization and breaking of chemical bonds of the polymeric chains, [1]. Gamma irradiation of such materials induces a crystallization effect, as confirmed by NMR, [2].…”
Section: Introductionmentioning
confidence: 70%
“…Initially, due to their outdoor durability, polymers were considered as an alternative to replace other types of materials [4]. Currently, the mentioned advantages have also caused an adverse environmental impact which is evidenced in landfills with a massive volume of plastic waste [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we must mention the most important index used in order to quantify the degree of photodegradation of polyolefin composites, namely the carbonyl index (CI) [15,16]. This index is calculated from the ratio between the absorbance of carbonyl groups (generated during photodegradation) stretching vibrations and the absorbance of methylene scissoring (characteristic to polyolefin materials): In all the cases, CI increases during exposure to light due to the photo-oxidative processes, as can be observed from the figure 8.…”
Section: Polyethylene Photodegradationmentioning
confidence: 99%